ANALISA LAJU SEBARAN YIELD SEDIMEN PADA DTA WADUK SAGULING DENGAN MENGGUNAKAN PENDEKATAN USLE-GIS - Juan Indra; Suharyanto Suharyanto (Wahana Teknik Sipil: Jurnal Pengembangan Teknik Sipil, 2022)
One of the issues that is still a problem in the upstream watershed, including thewater catchment area of Saguling Reservoir, is land use change. Changes in landuse in water catchment conservation areas into economic, industrial and residentialareas, will cause an increase in run-off during the rainy season and sedimenttransport to the reservoir inlet, while changes in land use downstream of thereservoir will cause an increase in demand. Therefore, research is needed todetermine the rate of increase in sediment yield that occurs in the watershed of theSaguling Reservoir. The integration of USLE and GIS allows us to determine thespatial distribution of parameters. Each factor in USLE is calculated using theexisting facilities in the GIS software. The results showed that there was anincreasing rate of sediment yield in the "Very Heavy" TBE category, while in the"Medium" TBE category the trend of sediment yields showed a downward trend.